MODEL PENGUKURAN KINERJA EKONOMI DAN KEMANDIRIAN KEUANGAN DAERAH KABUPATEN/KOTA DI JAWA TIMUR - Sudarti, Sudarti; Malik, Nazaruddin; Sutikno, Sutikno (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
The research objective is to measure the economic performance and financial independence of the respective districts or cities in East Java Province. To measure it , the author used physical and non physica abilitie, economic and business sector growth , area quality of growth, and financial independence. The benefit is to contribute the development of alternative models of economic performance measurement and financial independence for Regency/City, the form of software measurement of economic performance and financial independence of the Regency/City.